2004
DOI: 10.1046/j.8755-8920.2003.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblasts and Soluble Adhesion Molecules in Peripheral Blood of Women with Pregnancy‐Induced Hypertension

Abstract: The increased number of trophoblast cells in maternal peripheral blood and higher levels of sVCAM-1 correlate with the presence of PIH. The differences of sVCAM levels were significantly higher than those observed for sICAM. The results indicate an association between circulating trophoblasts and vascular endothelium activation, during PIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
1
7
0
2
Order By: Relevance
“…Previous studies have shown that there was an increase of CFTCs in PE (Heimrath et al, 2004). We also found concordant results in that PE patients displayed higher number of CFTCs than control subjects.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Previous studies have shown that there was an increase of CFTCs in PE (Heimrath et al, 2004). We also found concordant results in that PE patients displayed higher number of CFTCs than control subjects.…”
Section: Discussionsupporting
confidence: 88%
“…As previously pointed out (Hahn and Holzgreve, 2002b), the placental lesions leading to the increased traffic of fetal cells into the maternal periphery occur early in those pregnancies which subsequently develop preeclampsia. Moreover, the vascular endothelium is activated during pregnancy-induced hypertension, and the amount of circulating trophoblasts is related to its activation status (Heimrath et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathology can result in high resistance in placental vessels, significantly reducing placental blood flow. Impaired placental perfusion leads to fetal growth retardation, activation of inflammatory response cascade and damaging of endothelium [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction of vascular endothelium in PIH women is accompanied by elevated amounts of syncytiotrophoblast particles and increased levels of several soluble adhesion molecules, e.g., sVCAM and sICAM, in peripheral blood (Heimrath et al 2004). Other studies have shown that concentration of serum vascular endothelial growth factor (VEGF), von Willebrand factor and fibronectin was also elevated.…”
Section: Introductionmentioning
confidence: 99%